Odpowiedź :
3. a) 4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3-4+3
-3x=-9
x=3
b)3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-3-4
-6x=-6
x=1
c)-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+1+3
-4x=8
x=-2
d)-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x= -3+1+8+3
-3x=9
x=-3
4. a) 3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-4-8+5+4-3
-3x=-6
x=2
b)4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=3-7+4+3-4
x=-1
c)4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x=4+6+7-8+5
7x=14
x=2
d) -4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=-7-5-1+4+4
-8x=-5
x=5/8
5.a)3x-12-8x+28=2x+10
3x-8x-2x=10-28+12
-7x=-6
x=6/7
b)4x-6+12-3x=-x-1
4x-3x+x=-1-12+6
2x=-7
x=-3.5
c)2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-2-6+12+6
-3x=10
x=-3 1/2
d)6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-4-2-6-6
-2x=-18
x=9
6. a) 2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=-18+12+6+14
-7x=14
x=-2
b)-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=72-8+48+18
-26x=130
x=-5
c)-8x-16+3x+15=-4x-6+8x-4
-8x+3x+4x-8x=-4-6-15+16
-9x=-9
x=1
d) 24-6x+10x-25=4x-1-12+3x
-6x+10x-4x-4x=-12-1+25-24
-4x=-12
x=3
7. a) 9-3x+2x=8-2x+2
-3x+2x+2x=2+8-9
-x=1
x=-1
b)4x+5-3x-6=4+2x-4
4x-3x-2x=-4+4+6-5
-x=1
x=-1
c)4-15+5x=-x-3+2x
5x+x-2x=-3+15-4
4x=8
x=2
d)x-7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6
x=-2